Renal Transplant Acute Rejection with Lower Mycophenolate Mofetil Dosing and Proton Pump Inhibitors or Histamine‐2 Receptor Antagonists. Issue 12 (28th November 2017) - Patel, Kajal S.; Stephany, Brian R.; Barnes, Julie F.; Bauer, Seth R.; Spinner, Michael L.
Abstract : Background: Pharmacokinetic data show reduced mycophenolic acid levels in renal transplant recipients taking mycophenolate mofetil (MMF) and proton pump inhibitors (PPIs) concomitantly. This reduced exposure could increase rejection risk. The typical initial MMF dose post renal transplantation is 2 g/day, which often requires dose reduction secondary to side effects. Existing studies have not shown significant acute rejection differences for patients taking MMF‐PPI versus patients taking MMF‐ranitidine. Objective: The purpose of this study was to evaluate clinical outcomes in renal transplant recipients receiving a lower MMF dose than previously studied (1.5 g/day) and either a PPI or histamine‐2 receptor antagonist (H2RA). Methods: This retrospective cohort study included adult subjects receiving a renal transplant between January 1, 2009, and June 30, 2013. Comparison groups were defined based on acid‐suppressing therapy class prescribed at discharge from transplantation. The primary outcome was acute rejection incidence within 1 year posttransplantation. Results: Of 728 renal transplant recipients screened, 522 were included: 183 taking a PPI and 339 taking an H2RA. There was no significant difference in acute rejection within 1 year (H2RA 19% versus PPI 14%, p=0.12) or 3 months (4% vs 5%, p=0.44, respectively) posttransplantation. Maintenance immunosuppression (MMF dose and tacrolimus troughs) was similar between groups at 3 months and 1 year. Graft and patient survivals were favorable (> 95%), and graft function at 1 year was stable and similar between groups. Conclusion: Despite taking lower MMF doses than previously studied, subjects on a PPI compared to an H2RA were not at increased risk of acute rejection within 1 year posttransplantation.